LITERATUR REVIEW : ANALISIS FAKTOR FAKTOR YANG BERHUBUNGAN DENGAN DAMPAK KESEHATAN TERHADAP PERTAMBANGAN - Marwiyah Berutu; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
According to Susanto and Setyowati (2002), mining is a series of activities that include searching, mining (digging), processing, using, and selling excavated commodities (minerals, coal, geothermal, oil, and gas). Land clearing and landscape modification are other important aspects of coal mining that may have negative impacts on the ecology, economy and social structure of communities. Ecological decarbonization effects include landscape changes, decreased soil fertility, threats to biodiversity, decreased water quality, decreased air quality, and pollution. Conflicts between communities and companies, declining public health, shifts in people's mindsets, and adjustments to the social structure of communities are only a small part of the social impacts of mining. The health effects of coal mining include skin conditions and ARI in humans.